ANALISIS SISTEM REKRUTMEN TERHADAP KUALITAS KERJA KARYAWAN PADA PT. BATARA INDAH DI MAKASSAR - Husnawati Rahman (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to determine Is the recruitment system affects the quality of employees at PT. Batara Indah in Makassar. As for the method of analysis used in this study is a simple linear regression analysis is an analysis to determine the effect on the quality of the system of recruitment of employees. Based on the analysis and pembahaasn the recruitment effect on the quality of employees, it can be drawn some conclusions from the analysis that is Based on a regression analysis of the obtained value Y = 8941 + 0.833 X, it can be interpreted that the values ​​bo = 8.941, this can be interpreted that without the recruitment of the employees' quality of 8.941%, while the value of value b1 = 0.832 which means that if PT. Batara Indah in Makassar increase rekrukmen it will affect the quality of work of employees. While From the analysis of the obtained values ​​of correlation r Square or determination coefficient of 0.545 means that 54.5% of the variation kkualitas affected by the recruitment of employees, while the remaining 45.5% is influenced by other factors not examined in this study. The correlation coefficient R = 0.738 showed that the correlation between recruitment and the quality of employees is positive. This means that if the recruitment improved the quality of employees increased